Effect of Self-Acupressure on Fatigue in Patients with Multiple Sclerosis - Yeni, Kubra; Tulek, Zeliha; Terzi, Murat (Elsevier Sci Ltd, 2022)
Aim: This study was conducted as a randomized controlled study to evaluate the effect of self-acupressure on fatigue in patients with Multiple Sclerosis (MS). Method: The sample of the study consisted of 123 patients (41 in the experiment group, 40 in the sham group, and 42 controls) who were admitted to a neurology clinic in a university hospital. To collect data a patient information form, Fatigue Severity Scale (FSS), Expanded Disability Status Scale (EDSS), and Mini-Mental Status Examination were used. Depressive mood and sleep quality, which may affect fatigue, were evaluated using the Beck Depression Scale (BDI-II) and Pittsburg Sleep Quality Index (PSQI), respectively. The patients in the experimental group were applied acupressure by use of LI4 (He Gu), SP6 (San Yin Jiao) and ST36 (Zu San Li) points. Results: The majority of patients were female (67.5%) and the mean age was 41.18. In addition, the mean BDI-II score of the patients was found to be 15.54, and the mean score of PSQI was 6.78 and the mean scores of these scales were similar in all groups. When the baseline FSS score means were examined, there was no significant difference among the groups (Acupressure:5.54 +/- 0.87, Control:5.40 +/- 0.92, and Sham:5.50 +/- 0.99; p = 0.816). In the 4th week, there was a significant decrease in the mean score of fatigue of the experimental group compared to the other two groups (Acupressure:4.15 +/- 1.09, Control:5.47 +/- 1.11, Sham:5.34 +/- 1.14, p < 0,001). Conclusion: Our results suggest that acupressure might be an effective method to reduce fatigue in patients with MS.
Tulek, Zeliha/0000-0001-8186-6698; Yeni, Kubra/0000-0003-1098-5619
Keywords: Acupressure; Multiple Sclerosis; Fatigue; Sleep; Depression